Superficial radial artery- a rare variation and its clinical significance - P K Sankaran; Gunapriya Raghunath; Parimelazhagan; R Sathyan (Wolters Kluwer Medknow Publications, 2014)
During routine dissection of upper limb, a variation in the origin of radial artery was observed in a female cadaver of about 60 years. The radial artery is usually a smaller terminal branch of the brachial artery in the forearm. On the right side of the cadaver the radial artery was found to originate from second part of the axillary artery, whereas on the left side the origin of radial artery was found to be normal. This variant of radial artery has been rarely documented in literature. Accurate anatomy of radial artery and its variations have definite diagnostic, interventional, and surgical significance.